2022
DOI: 10.1002/hup.2841
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of memantine's efficacy and safety in the treatment of children with autism spectrum disorder: A systematic review and meta‐analysis

Abstract: Background:The United States Food and Drug Administration has approved drugs that address only autism-related symptoms rather than the underlying impairments.N-Methyl-D-Aspartate receptor antagonists have recently emerged as a promising treatment option for a variety of neurologic and developmental problems, including autism. Aims:To review (systematically), for the first time, the medical literature that explores the safety in and efficacy of memantine in autism. Methods and procedures:A comprehensive electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…One approach is to inhibit the release of glutamate, as seen with the drug riluzole. Another strategy is to decrease glutamate signaling through the use of NMDAR antagonists, such as acamprosate (which also antagonizes mGluR5 and GABAB) and memantine [60,61]. While some studies have shown promising results for glutamate therapy in improving ASD symptoms and cognitive function, more research is needed to establish its safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…One approach is to inhibit the release of glutamate, as seen with the drug riluzole. Another strategy is to decrease glutamate signaling through the use of NMDAR antagonists, such as acamprosate (which also antagonizes mGluR5 and GABAB) and memantine [60,61]. While some studies have shown promising results for glutamate therapy in improving ASD symptoms and cognitive function, more research is needed to establish its safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Won et al, have shown that enhancing NMDA-R function can improve autistic-like behavior in genetically mutated mice (Shank2-mutant) [ 83 ]. On the contrary, some evidence demonstrated that elevated NMDAR function is also involved in ASDs and administration of NMDA-R antagonists improved ASD-related symptoms [ 20 , 21 ]. Several previous studies have shown that MS increased the gene expression of NMDA-R subunits (NR2A and NR2B) in the brain [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, some evidence demonstrated that elevated NMDA-R function is also involved in ASDs. In this concept, it has been shown that Memantine, an NMDA-R antagonist, improved ASD-related symptoms [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%